The Impacts of Company Financial Performance and Auditor Switching on Going Concern Audit Opinion - Suci Nurulita; Fitri Humairoh (Politeknik Caltex Riau, 2023)
A going concern audit opinion is an additional opinion issued by an independent auditor regarding doubts about the viability of a company that takes place in less than one year of audited financial reporting. In giving this opinion there are many problems, one of them is the survival of the company which is difficult to predict so that the auditor is not easy to give this opinion even though there are clear guidelines that regulate it. The purpose of this study is to analyze the factors that influence going concern audit opinion in the form of auditor switching and the company's financial performance which consists of company growth, liquidity and solvency. Manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2020 period make up the population and this research. Based on the results of selecting samples using purposive sampling method, it was found that 33 companies were selected in this study. The findings in this study are based on the results of logistic regression analysis testing showing that the company's financial performance in the form of company growth, liquidity and solvency have an influence on giving a going concern audit opinion but not on Auditor Switching.